Computer Science - Theory and Applications 17th International Computer Science Symposium in Russia, CSR 2022, Virtual Event, June 29 - July 1, 2022, Proceedings - Kulikov, Alexander S.; Raskhodnikova, Sofya (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book constitutes the proceedings of the 17th International Computer Science Symposium in Russia, CSR 2022, held in St. Petersburg, Russia, June 29-July 3, 2022. The 21 full papers were carefully reviewed and selected from 51 submissions. The papers cover a broad range of topics, such as formal languages and automata theory, geometry and discrete structures; theory and algorithms for application domains and much more.
Optimization-friendly generic mechanisms without money -- Expanders in Higher Dimensions -- Private frequency estimation via projective geometry -- Parameterized Algorithms for Finding Highly Connected Solution -- Coloring a Dominating Set without Conflicts: q-Subset Square Coloring -- Quotient structures and groups computable in polynomial time -- Parameterized Complexity of List Coloring and Max Coloring -- Eternal Vertex Cover on Bipartite and Co-Bipartite Graphs -- Non-Crossing Shortest Paths in Undirected Unweighted Planar Graphs in Linear Time -- Kernelization of Same-Size Clustering -- Output Sensitive Fault Tolerant Maximum Matching -- Bounds for Synchronizing Markov Decision Processes -- Parameterized Complexity of Set-Restricted Disjoint Paths on Chordal Graphs -- Discrete versions of the KKM lemma and their PPAD-completeness -- The Fast Algorithm for Online k-server Problem on Trees -- Finite Ambiguity and Finite Sequentiality in Weighted Automata over Fields -- Bounds for the Flock-of-Birds Problem -- Heterogeneous Multi-Commodity Network Flows Over Time -- On the determinization of event-clock input-driven pushdown automata -- optimization -- graph theory -- algorithms -- parameterized complexity -- group theory -- complexity theory -- grammars and context-free languages -- computational geometry -- quantum computation theory.
Keywords: Computer science; Theory of Computation